Fuzzy inference system for the identification of over-the-counter (otc) drugs. (2013)
This document shows the details of the implementation of a fuzzy inference system, for the identification of four over-the-counter drugs (Naproxen, Calcium Carbonate, Muvett and Winadol), by using a Raman Spectroscopy, which output is the characterization of the substance. Data obtained from Raman Spectroscopy are modeled with Matlab®- Fuzzy Logic Toolbox.